How does monetary policy influence bank lending? Evidence from the market for banks' wholesale funding - Max Breitenlechner; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2018)
We study the transmission of monetary policy shocks to loan volumes using a structural VAR. To disentangle different transmission channels, we use aggregated data from the market for large certificates of deposits and apply a sign restrictions approach. We find that although the standard bank lending channel as well as the recently formulated risk-pricing channel (Disyatat, 2011; Kishan and Opiela, 2012) contribute to the transmission of policy shocks, the effects associated with the risk-pricing channel are quantitatively stronger. Our results also show that policy shocks give rise to non-negligible effects on loan demand.
Keywords: C32; E44; E52; 330; bank lending channel; risk-pricing channel; external finance premium; structural vector autoregression; sign restrictions